Inteligência emocional e avaliação de desempenho em estágio acadêmico de cursos da área da saúde - Pereira, Fernanda Esteves (Universidade Federal de São Carlos, 2020)
This study aimed to verify the relationship between emotional intelligence and its facets with academic internship performance of students enrolled in specific mandatory internships in the curriculum of Medicine, Psychology, Nursing, Physiotherapy and Occupational Therapy courses. The study included 74 students with a mean age of 23.65 (SD = 3.651, Md = 23.00), with a minimum of 19 years and a maximum of 48 years, 68.9% being female. The instruments used were: Emotional Intelligence Battery, Student Assessment according to Academic Internship Supervisors (adapted), Student Self-Assessment in Academic Internship (adapted) and Academic Internship Notes. Participants were divided into two groups: G1 – Medicine, Nursing, Physiotherapy and Occupational Therapy, with 44 participants (59.6%), in which 63.6% were female; and G2 – Psychology, with 30 participants (40.5%), in which 76.7% were women. Due to the low adherence of professors' responses to the Student Assessment questionnaire according to their Academic Internship Supervisors, this instrument was not included in the data analysis of this research. For data analysis, descriptive statistics were performed to characterize the sample and inferential analyzes to investigate the reformulated hypotheses. The results indicated that there was a significant, positive and moderate correlation between Comprehension of Total Emotions and Student Self-Assessment in Academic Internship for G2 – Psychology (hypothesis partially accepted). There was a significant, positive and moderate correlation between Comprehension of Emotions A and Grades in Academic Stage for the general sample and a significant, positive and strong correlation between Understanding of Emotions A and Grades in Academic Stage for G1 (hypothesis partially accepted). It was also possible to identify a significant, negative and strong correlation between Perception of Emotions per se and Grades in Academic Internship for women in the general sample and a positive, significant and strong correlation between Emotion Regulation and Student Self-Assessment in Academic Internship for men in the sample general. In addition, there was a significant, negative and very strong correlation between Comprehension of Total Emotions and Academic Internship Grades and a significant, positive and very strong correlation between AE Emotions Understanding and Academic Internship Grades for G2 men. There was still a significant, negative and very strong correlation between Perception of Emotions in the Other and Grade in Academic Internship and a significant, negative and very strong correlation between Regulation of Emotions and Grade in Academic Internship for women in G1. For women in G2, there was a significant, positive and moderate correlation between Comprehension of Total Emotions and Student Self-Assessment in Academic Internship (hypothesis partially accepted). This study contributed to the investigations of emotional intelligence in interns in health care courses, as well as to the relationship between emotional intelligence and academic performance in internships, a topic that is still little studied, especially in Brazil.
Emotional intelligence and performance assessment in academic internship of health area courses
Keywords: Inteligência emocional; Avaliação de desempenho; Cursos da área da saúde; Emotional intelligence; Performance - Evaluation; Health service areas; CIENCIAS HUMANAS::PSICOLOGIA